Case Report: Micro-RNAs in Plasma From Bilateral Inferior Petrosal Sinus Sampling and Peripheral Blood From Corticotroph Pituitary Neuroendocrine Tumors - Niedra, Helvijs; Peculis, Raitis; Konrade, Ilze; Balcere, Inga; Romanovs, Mihails; Steina, Liva; Stukens, Janis; Sokolovska, Jelizaveta; Klovins, Janis; Rovite, Vita (Frontiers in Endocrinology, 2022)
Objective: Circulating miRNAs are found in bodily fluids including plasma and can serve as biomarkers for diseases. The aim of this study was to provide the first insight into the landscape of circulating miRNAs in close proximity to the adrenocorticotropic hormone (ACTH) secreting PitNET. To achieve this objective next-generation sequencing of miRNAs in plasma from bilateral inferior petrosal sinus sampling (BIPSS) - a gold standard in diagnosing ACTH-secreting PitNETs was carried out and selected miRNA candidates were further tested by RT-qPCR in independent patient cohorts. Methods: Sinistral (left) and dextral (right) BIPSS blood samples of the patient were collected in three time points: before the administration of corticotropin-releasing hormone, 5 and 15 minutes after stimulation. In differential expression analysis, sinistral plasma was compared with dextral. The selected miRNA candidates were tested in plasma by RT-qPCR in two patient groups: 1) in five ACTH secreting PitNET patients with plasma samples taken before and 24 hours after surgery, 2) in 12 ACTH secreting PitNET patients vs. 9 non-functioning PitNET patients. Results: BIPSS concluded that the highest amount of ACTH was released in the sinistral side at the 5th minute mark indicating a presence of a tumor. The highest amount of differentially expressed miRNAs was observed 5 minutes after stimulation (20 upregulated, 14 downregulated). At the 5th minute mark in sinistral plasma, two miRNAs were identified: hsa-miR-7-5p and hsa-miR-375-3p that were highly upregulated compared to other BIPSS samples and peripheral plasma samples. Further testing by qPCR revealed significant reduction of miR-7-5p in plasma 24 hours after surgery and upregulation in plasma of ACTH secreting PitNET patients compared to non-functioning PitNET patients (P =0.0013). Conclusions: By stimulating the ACTH secreting PitNET with CRH a rapid increase of two miRNAs (hsa-mir-7-5p, hsa-mir-375-3p) and ACTH can be observed in sinistral inferior petrosal (tumor side). A decrease of miR-7-5p in plasma after surgery and upregulation in plasma of ACTH secreting PitNET patients was discovered implying that further studies of this miRNA as diagnostic marker is needed.